Gray-White Matter Ratio at the Level of the Basal Ganglia as a Predictor of Neurologic Outcomes in Cardiac Arrest Survivors: A Literature Review - Zhou, Fating; Wang, Hongxia; Jian, Mengyao; Wang, Zhiyuan; He, Yarong; Duan, Haizhen; Gan, Lu; Cao, Yu (Frontiers in Medicine, 2022)
Loss of gray-white matter discrimination is the early image feature of cranial computer tomography in cardiac arrest survivors, and it has been also regarded as a novel predictor for evaluating the neurologic outcome. As displaying clearly in computer tomography and sensitive to hypoxia, gray-white matter ratio at basal ganglia (GWR-BG) region was frequently detected to assess the neurologic outcome by several studies. The specificity of GWR-BG is 72.4% to 100%, while the sensitivity is significantly different. Here we review the mechanism of cerebral edema following cardiac arrest, demonstrate the determination procedure of GWR-BG, summarize the related research about GWR-BG predicting neurologic outcome of cardiac arrest survivors, and discuss those factors associated with predicting accuracy. Finally, we describe the effective measurements to increase the sensitivity of GWR-BG in predicting neurologic outcome.